Docentes de Terra Nova-Ba: entre os dizeres e o silêncio frente aos pressupostos da lei 10.639/03 - Araújo, Gizele dos Santos Belmon (2018)
This research seeks to investigate the relationship of the teachers with the assumptions established by Federal Law 10.639/03 amending article 26 A of the law of guidelines and Bases of education – LDB, which versa on the compulsory teaching of history and culture Brazilian and African in basic education. And the specific objectives are as follows: 1. Identify whether teachers know the assumptions established by Federal Law 10.639/03; 2. Recognizing how those teachers who claimed to know the law in question, seize their assumptions and how this is reflected in their pedagogical practices; 3. Notice among the teachers who said they have forgotten the law 10.639/03, the possible reason of this forgetfulness. The teachers, subjects of the research, are those who teach at the school Marguerida Maria Lisboa de Oliveira serving children of the age group between 4 and 5 years of child education and the 1st and 2nd year of elementary School. The research, of a qualitative character, had as instruments of data collection The Interstructured interview and the Analysis of legal documents (printed and digital) that are versed in the law 10.639/03 or that serve it on the basis, taking as main categories of analysis the concepts of Prejudice (GOMES, 2005), forgetfulness (BARRONCAS, 2012), (ARAÚJO SANTOS, 2007), and silencing (MULLER; COSTA, 2016). In the present research, the methodology used in the treatment with the oral sources was the oral history methodology as well as the use of Etnotexto as one of the methods in the work with oral sources (JOUTARD, 2000), (GANDON, 2001).The results of the research point to, on the one hand, the forgetting of Law 10.639 / 03 by the teachers reveal painful experiences of ethnic-racial prejudice suffered by them; on the other hand, the frequent contradictions in the actions of professors who claim tobe consistent with the aforementioned Law. Finally, these questions become even more pertinent when the religious factor that comes into play, which ends up interfering in a peculiar and complex way in the processes of effecting the Law 10.639 / 03